Fiscal policies and the prices of labor: A comparison of the U.K. and U.S. - Casey Mulligan (IZA Journal of Labor Policy, 2015)
This paper measures the 2007-13 evolution of employment tax rates in the U.K. and the U.S. The U.S. changes are greater, in the direction of taxing a greater fraction of the value created by employment, and primarily achieved with new implicit tax rates. Even though both countries implemented a temporary "fiscal stimulus," their tax rate dynamics were different: the U.S. stimulus increased rates, whereas the U.K. stimulus reduced them. The U.K. later increased the tax on employment during its "austerity" period. Tax rate measurements are a first ingredient for cross-country comparisons of labor markets during and after the financial crisis.
Keywords: E24; H31; I38; J22; 330; Marginal tax rates; Employment; International comparisons